For whose benefit? : the everyday realities of welfare reform / Ruth Patrick. - Patrick, Ruth (Policy Press, 2017)
For Whose Benefit? explores how those at the sharp end of welfare reform experience changes to the benefit system. It looks at how the rights and responsibilities of citizenship are experienced on the ground, and whether the welfare state still offers meaningful protection and security to those who rely upon it.